Research on microseismic source location based on time quality constraints - Wu, Xuefei; Xie, Qian; Yan, Junsheng (Frontiers in Earth Science, 2024)
IntroductionTo develop a small-scale regional microseismic location model for coal mines and enhance the accuracy of microseismic location at the bottom plate,this article proposes a high-precision location algorithm for 3D-Fast Sweeping Method (3D-FSM) seismic sources under time quality constraints.MethodsThe study investigates the numerical simulation of microseismic location accuracy on coal seam floor, considering various observation systems, arrival time picking errors, and wave velocity discrepancies. The algorithm employs a VGG-16 deep learning network to train and establish a quality control model for P-wave pickup values; Next, utilizing the 3D-FSM framework, it calculate the seismic wave travel time field and applies Fermat’s principle for each detection point, as well as the reversible principle of elastic wave propagation path. This allows for the determination of the spatial path and travel time from any potential source point to the detection point. Finally, the algorithm scans each computational node, using the controlled travel time difference to identify the source point corresponding to the smallest spatial node.ResultsThe results indicate that the location error of the borehole tunnel observation system is smaller than that of the tunnel observation system. Specifically, with the borehole tunnel observation system, the variance in P-wave arrival time picking is 1 ms, and the wave velocity variance is 20 m/s2, demonstrating high accuracy.DiscussionThe findings suggest that the 3D-FSM seismic source location algorithm, under quality control, approaches the precision of manual location methods and exhibits high reliability, even when disregarding significant accuracy errors during the quality control location process.